Communicating leakage risk in the hydrogen economy: Lessons already learned from geoenergy industries - Stalker, Linda; Roberts, Jennifer J.; Mabon, Leslie; Hartley, Patrick G. (Frontiers in Energy Research, 2022)
Hydrogen is set to play a part in delivering a net zero emissions future globally. Currently, hydrogen production, storage, transport and utilisation are being explored to scope opportunities and to reduce barriers to market activation. One such barrier could be negative public response to hydrogen technologies. Previous research around socio-technical risks finds that societal acceptance issues are particularly challenging for emerging, remote, technical, sensitive, uncertain or unfamiliar technologies - such as hydrogen as a fuel. Thus, while the hydrogen value chain could offer a range of potential environmental, economic and social benefits, each will have perceived risks that could challenge the introduction and subsequent roll-out of hydrogen on an industrial scale. These potential issues must be identified and managed so that the hydrogen sector can develop, adapt or respond appropriately. Geological storage of hydrogen may be an important step in the value chain to manage hydrogen energy exports, however it could present challenges in terms of perceived safety. Valuable lessons can be learned from international research and practice of CO2 and natural gas storage in geological formations (for carbon capture and storage, [CCS], and for power, respectively) and for hydrogen storage in salt caverns or porous sandstones. Here, we explore these learnings. We consider the similarities and differences between these technologies, and how these may affect perceived risks. We also reflect on lessons for effective communication and community engagement. We draw on this to present potential risks to the perceived safety of - and societal acceptability of – the geological storage of hydrogen. One of the key lessons learned from CCS and natural gas storage is that progress is most effective when risk communication and societal and community acceptability are considered from the early stages of technology demonstration.